Dedicated optical systems of the Institute of Applied Optics - Litwin, Dariusz; Galas, Jacek; Daszkiewicz, Marek; Kryszczyński, Tadeusz; Czyżewski, Adam; Radziak, Kamil (Photonics Letters of Poland, 2019)
The paper presents a collection of selected optical systems recently developed in the Institute of Applied Optics-INOS. The collection includes the family of techniques where the continuously modified wavelength facilitates high accuracy measurements of optical and geometrical features of the object in question i.e. the variable wavelength interferometry and confocal chromatic sensors. In addition, the paper refers to the construction of a new type of a spectrometer with rotating plasma and an illumination system supporting the road safety. Full Text: PDF References M. Pluta, Advanced Light Microscopy (Vol. 3, PWN, Elsevier, Warszawa-Amsterdam-London-New York-Tokyo, 1993). DirectLink M. Pluta, "Object-adapted variable-wavelength interferometry. I. Theoretical basis", Journal of Opt. Soc. Am., A4(11), 2107 (1987). CrossRef M. Pluta, "Variable wavelength microinterferometry of textile fibres", J. Microscopy, 149(2), 97 (1988). CrossRef M. Pluta, "On double‐refracting microinterferometers which suffer from a variable interfringe spacing across the image plane", Journal of Microscopy, 145(2), 191 (1987). CrossRef K. A. El-Farahaty, A. M. Sadik, A. M. Hezma, "Study of Optical and Structure Properties of Polyester (PET) and Copolyester (PETG) Fibers by Interferometry", International Journal of Polymeric Materials 56(7),715 (2007). CrossRef J. Galas, D. Litwin, M. Daszkiewicz, "New approach for identifying the zero-order fringe in variable wavelength interferometry", Proc. SPIE 10142, 101421R (2016). CrossRef A. Sadik, W. A. Ramadan, D. Litwin, "Variable incidence angle method combined with Pluta polarizing interference microscope for refractive index and thickness measurement of single-medium fibres", Measurement Science and Technology, IOP Publishing 14(10), 1753 (2003). CrossRef J. Galas, S. Sitarek; D. Litwin; M. Daszkiewicz, "Fringe image analysis for variable wavelength interferometry", Proc. SPIE 10445, 1044504 (2017). CrossRef D. Litwin, A. M. Sadik, "Computer-aided variable wavelength Fourier transform polarizing microscopy of birefringent fibers.", Optica Applicata 28(2), 139 (1998). DirectLink D. Litwin, J. Galas, N. Błocki, "Automated variable wavelength interferometry in reflected light mode", Proc.SPIE 6188, 61880F (2006). CrossRef M. Pluta, "Variable wavelength interferometry of birefringent retarders", Opt. Laser Technology, 19(3), 131 (1987). CrossRef K. Fladischer et al. "An ellipsoidal mirror for focusing neutral atomic and molecular beams", New journal of Physics, 12(3) 033018 (2010). CrossRef K. Fladischer et al. "An optical profilometer for characterizing complex surfaces under high vacuum conditions", Precision engineering Elsevier 32(3), 182 (2008). CrossRef A.E. Weeks et al. "Accurate surface profilometry of ultrathin wafers", Semiconductor Science and Technology", IOP Publishing, 22(9), 997 (2007). CrossRef D. Litwin et al. "Overview of the measuring systems where a continuously altered light source plays a key role: Part I", Proc. SPIE 10808, 10 8080B (2018). CrossRef D. Litwin et al. "Noise reduction in an optical emission spectrometer with rotating diffraction grating", Proc. SPIE 10142 101421Q (2016). CrossRef D. Litwin et al. "Photonics approach to traffic signs", Proc SPIE 10142 1014214, (2016). CrossRef